EDITORIAL - Yang, Sam (Revista de Engenharia Térmica, 2016)
The editorial of Engenharia Térmica of this issue continues the discussion on scientific research needs in vital areas in which thermal engineering has important participation. The main goal is to motivate the readers, within their specialties, to identify possible subjects for their future research. Extensive research efforts have been devoted to the development of high performance heat sinks, and numerous geometric designs and fin arrangements as well as materials have been proposed to achieve higher heat dissipation rates. Previous studies have deduced different fin geometries and arrangements based on minimum entropy generation or maximum heat transfer rate, subject to various constraints such as available space, material, or cost. Consequently, many fin shapes and arrangements exist in literature ranging from elliptical cylinders to rhombus, and from pin to flared fin, respectively. According to the literature review, however, helical fins have not yet been explored as an alternative design owing to its complex geometry that restricts the analysis to 3D space. Therefore, a 3D helical fin model still needs to be developed to investigate its feasibility and performance as an alternative fin design. In addition, a helical fin arrangements optimization study shall be conducted for minimum pressure drop and maximum heat transfer. The mission of Engenharia Térmica is to document the scientific progress in areas related to thermal engineering (e.g., energy, oil and renewable fuels). We are confident that we will continue to receive articles’ submissions that contribute to the progress of science.